2010
DOI: 10.1111/j.1365-2648.2010.05491.x
|View full text |Cite
|
Sign up to set email alerts
|

Home care nurses’ decisions about the need for and amount of service at the end of life

Abstract: Findings highlight the role of considerations of family caregiver capacity, the influence of relationships and the importance of the context of practice, as part of a complete understanding of the complexity of access to care at the end of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(80 citation statements)
references
References 36 publications
5
73
0
2
Order By: Relevance
“…Nursing practice in HC is influenced both by patient profile and by the logic peculiar to homes. In HC, nurses offer care to a diverse profile, with a predominance of patients under palliative care (12)(13)22,27,33,50,52,55) and the elderly (16,(28)(29)35) being noticed in this review, although analyzed articles have also reported care actions for children (11,19,25) and young individuals (28) with complex needs, as well as mentally challenged persons (14,27) . Review of the articles revealed that nurses conduct various actions in HC, such as: interpersonal support; health education for patients, family members; and caregivers; performance of technical procedures; and clinical and administrative supervision, as demonstrated in Chart 1.…”
Section: Nursing Actions In Home Carementioning
confidence: 96%
See 3 more Smart Citations
“…Nursing practice in HC is influenced both by patient profile and by the logic peculiar to homes. In HC, nurses offer care to a diverse profile, with a predominance of patients under palliative care (12)(13)22,27,33,50,52,55) and the elderly (16,(28)(29)35) being noticed in this review, although analyzed articles have also reported care actions for children (11,19,25) and young individuals (28) with complex needs, as well as mentally challenged persons (14,27) . Review of the articles revealed that nurses conduct various actions in HC, such as: interpersonal support; health education for patients, family members; and caregivers; performance of technical procedures; and clinical and administrative supervision, as demonstrated in Chart 1.…”
Section: Nursing Actions In Home Carementioning
confidence: 96%
“…Analysis of the articles shows that nurses have a central role in HC (13,25,27,33,40,46) . The relevance of their practice is in the fact that they are considered clinical specialists (11,27,34,56) , coordinators of care (12,15,27,34,40,43) , and case managers (15,40,43) , responsible for offering various care practices to patients (40) and also for performing important leadership roles (27,40) .…”
Section: Nursing Actions In Home Carementioning
confidence: 99%
See 2 more Smart Citations
“…Side effects appear to be an important issue, making family members feel fearful and helpless (Hinds, 1992;Hanson, Danis, Garrett, 1997;Lau et al, 2010). Dissemination of information and psychological support, especially for such negative events such as side effects, are of great importance to families (Hileman, Lackey, Hassanein, 1992;Hinds, 1992;Addington-Hall, McCarthy, 1995;Gelfman, Meier, Morrison, 2008;Stajduhar et al, 2011), given the fact that family members evaluate symptoms as significantly worse than professionals (Higginson, Wade, McCarthy, 1990). Therefore, it is crucial for palliative services to offer individual practical training and educational consultations for family members, and to adjust the content of these resources continuously to suit the unique needs of families (Hudson, 2009).…”
Section: Discussionmentioning
confidence: 99%